Anti-Corruption Education at Elementary Education as Primary Prevention of Corruptive Behavior: Study of Social Control Theory in Madura Indonesia - Effendi, Tolib; Octarina, Nynda Fatmawati; Hardinanto, Aris (International Journal of Psychosocial Rehabilitation, 2020)
This research was conducted to measure the role of anti-corruption education at the level of elementary education as an effort to prevent primary corrupt behavior in Madura, Indonesia. The method used in this research is socio legal research or non-doctrinal research using primary data based on interviews, questionnaires and direct observations in four districts in the Madura region. The results of this study are, that primary prevention efforts against corruption through anti-corruption education at the level of elementary education have not been running optimally because the existing processes have not been carried out thoroughly and systematically. Based on Travis Hirschi’s social control theory, anti-corruption education can be a way to increase students attachment and involvement in trusting anti-corruption values early on, so that corrupt behavior can be controlled as students ties with the school environment increase. The existence of integrative anti-corruption education in the curriculum and behavior outside the classroom will be an appropriate social control to suppress corruptive behavior in the Madura region.